2023
DOI: 10.1088/1755-1315/1196/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Energy Retrofit of Public Educational Buildings and Sustainable Mobility: Case study in Crete

C Heracleous,
A Kyriakidis,
G M. Stavrakakis
et al.

Abstract: The European Union, through the Energy Performance of Buildings Directive and the Energy Efficiency Directive, has been establishing requirements and expectations regarding energy savings and efficiency in buildings. Educational buildings comprise a significant part of public buildings that should lead the way in the energy retrofitting of existing building stock. The present study aims to create intelligent school complexes that will be energy upgraded to meet the need for reduced energy consumption in the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In line with the holistic approach to energy conservation, a novel addition to many modern retrofit practices is the provision of electric vehicle charging stations. While this addition does not directly impact the energy consumption of the building itself, it signifies a broader commitment to green and sustainable practices that extend beyond the building's immediate needs, reflecting a broader vision for a sustainable urban infrastructure [12].…”
Section: Technical Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with the holistic approach to energy conservation, a novel addition to many modern retrofit practices is the provision of electric vehicle charging stations. While this addition does not directly impact the energy consumption of the building itself, it signifies a broader commitment to green and sustainable practices that extend beyond the building's immediate needs, reflecting a broader vision for a sustainable urban infrastructure [12].…”
Section: Technical Interventionsmentioning
confidence: 99%
“…Heracleous et al ( 2023) [12] reported on the case study of a public school building constructed in 1980. They adopted a comprehensive approach to energy conservation was adopted, targeting both passive and active interventions.…”
Section: School Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations